Mg–3Zn–0.5Zr/HA nanocomposites fabricated by high shear solidification and equal channel angular extrusion. Issue 15 (13th October 2018) - Huang, Yan; Li, Junyi; Zhou, Li
ABSTRACT: Magnesium alloy matrix and hydroxyapatite (HA) nanoparticle reinforced composites for biomedical applications were fabricated by combined high shear solidification and equal channel angular extrusion (ECAE). The high shear treatment was performed immediately prior to casting at 680°C using a rotor–stator mechanism. The as-cast composite ingots were processed by ECAE at 300°C to various strains. The high shear treatment effectively reduced HA particle agglomeration and produced a fine grain structure for all HA contents. ECAE processing resulted in further grain refinement and an improved HA particle distribution, with the formation of a desirable HA dispersion. The composites with 3–5 wt-% HA displayed an optimum combination of strength and ductility, with a yield strength of 150–210 MPa and compressive reductions of 9∼13% before fracture.